Implementation of Collage Media Making Training to Improve Teachers' Pedagogical Skills in Early Childhood Islamic Education (PIAUD) in Gorontalo Regency - Munirah Munirah; Hairuddin; Irmawati Duko Ishak; Nazar Husain Hadi Pranata Wibawa (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Collage media creation training for Early Childhood Islamic Education (PIAUD) teachers in Gorontalo Regency was conducted to address the problem of teachers' low ability to design creative, effective, and contextual learning media. Based on an initial survey, 73% of teachers had never participated in collage training, 67% still relied on conventional media, and 58% did not understand media creation techniques.Objectives: This community service activity aimed to improve teachers' pedagogical competence in integrating local culture-based collage media into learning.Methods: The training involved 35 teachers as target partners and was implemented using the GOAD (Grouping, Observing, Analyzing, Designing, Doing) method through the preparation of teaching modules, collage media creation, group discussions, technical assistance, and learning simulations.Results: The results of the activity showed a significant increase in the knowledge and skills of teachers in managing classes, marked by an increase in the average score from 62.4 (pretest) to 87.8 (posttest). In addition, more than 85% of participants gave the training a "very good" rating. Teachers became more capable of creating safe, aesthetic, and contextual collage media and implementing them effectively in the classroom.Conclusion: This activity demonstrated that the training can improve teachers' pedagogical skills and thus support the quality of early childhood Islamic education.